Assessing the potential impact of an oral health education package integrated with augmented reality in improving oral health knowledge in children: a pre-post study design. - Rahmasari, Suci; Arini, Mustika; Khairani, Rahmi (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Augmented reality (AR) technology provides a novel approach to oral health education. This study examines the impact of AR-based educational tools on improving children's oral health knowledge, specifically assessing whether AR can significantly enhance knowledge compared to baseline. The primary objective is to determine if AR technology can increase oral health knowledge in children. Methods: This pre-experimental study used a pre-test and post-test design with a single group of 49 children aged 7 years. The AR-based tool was developed using the ADDIE model and implemented over two weeks. The effectiveness of the tool was assessed through a standardized oral health knowledge questionnaire, and data were analyzed using paired t-tests. Results: The results showed a significant increase in children's knowledge after the intervention, with mean scores rising from 5.27 (SD = 1.36) to 8.65 (SD = 0.9) (p < 0.05). The proportion of children with good knowledge increased from 8.2% to 88% post-intervention. Conclusion: The study demonstrates that AR-based tools can significantly improve children's oral health knowledge. This suggests that AR could be an effective educational medium in promoting better oral health practices among young learners.